To add incremental information: the main problem in cardiovascular risk evaluation - Clerico, Aldo; Lippi, Giuseppe (Journal of Laboratory and Precision Medicine, 2017)
Adrenomedullin (ADM) consists of 52 amino acids with a C-terminal amination and one intra-molecular disulfide bond between residues 16 and 21 (1,2) (Figure 1). This peptide hormone has been first isolated from human pheochromocytoma cells in 1993, hence its name (1). ADM is expressed and secreted by many tissues and organ systems, including cardiovascular, renal, pulmonary, cerebrovascular, gastrointestinal and endocrine tissues (2,3).